Análise comparativa do desgaste tribológico da liga Al 7075 e ligas ferrosas de baixo e médio carbono - SANTOS, Ernélison Angly da Silva (Universidade Federal do Oeste do Pará, 2024)
The main objective of this study is to analyze a comparative research about the tribological behavior of Al7075, AISI 1020 and AISI 1045 steels during the ball crater abrasion wear test without the presence of lubricants (abrasive slurry). The tests were performed for each alloy with a load equal to 1.4N, during 5, 10, 15 and 20 minutes and the rotation used was equal to 230 rpm. Scanning electron microcopy and optical microscopy were used to characterize the worn samples. The wear resistance was measured by calculating the worn volume (V), with the basis on the diameter of the crater produced by the rotating sphere. (Colaço, 2001). According to the results, the alloy Al7075 presented the lower wear resistance and the AISI 1020 and AISI 1045 steels obtained a similar wear behavior, probably due to the presence of carbon, which makes the hardness increase. However, when the sliding distance is about 276 m, the wear resistance of AISI 1045 steel falls indicating that AISI 1045 may present lower wear resistance for longer sliding distances